Local Community-based Tourism in The Frame Institutional Theory - Rentandatu, Benhur; Alwi, Alwi; Djabbari, Muhammad Hidayat (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2021)
The tourism sector is a strategic and superior sector that is the focus of development in supporting the regional economy of Merauke Regency. The tourist attractions of Merauke Regency include natural tourism, cultural tourism and artificial tourism. The wealth of tourism owned can be the main capital in the economic development of Merauke Regency. In addition, its tourism wealth also places Merauke Regency in a strategic position in the tourism constellation of the Unitary State of the Republic of Indonesia. For this reason, the development of local community-based tourism is important to do so as to increase community participation and improve the economy. This study aims to explain the network of local community-based tourism development policies in Merauke Regency based on three institutional pillars (regulative, normative and cultural-cognitive). This study uses a qualitative approach. Data was collected through interviews, observation and documentation studies. Data processing and analysis techniques were carried out with data reduction, data display, and conclusion drawing/verification. Determination of informants using purvosive sampling technique. The results of the study show that there is a regulatory synergy, namely the synergy of rules issued by the Merauke district government with the system of rules used in the life of indigenous peoples. Normative shows mentoring and community involvement around tourist sites for the development of skills and knowledge in tourism management, and cultural-cognitive shows the existence of shared knowledge and understanding related to developing economic aspects by creating production centers for the development of the potential of local communities in collaboration with the customs of indigenous peoples in producing their cultural products